Orienting Negative Politeness Strategies Towards the Hearer Negative Face in Disney’s Frozen Movie - Putu Ayu Anggita Gangga Swari; I Made Netra; Ketut Santi Indriani (IAI Nasional Laa Roiba Bogor, 2024)
The study aims to analyze the use of negative politeness strategies by characters in Disney's “Frozen” movie using Brown and Levinson's (1987) politeness theory, focusing on how these strategies address the hearer's negative face. The data of the research were taken from Disney's